The unmet needs of partners and caregivers of adults diagnosed with cancer: a systematic review. Issue 3 (6th July 2012) - Lambert, Sylvie D; Harrison, James D; Smith, Ellen; Bonevski, Billie; Carey, Mariko; Lawsin, Catalina; Paul, Chris; Girgis, Afaf
Abstract : Objectives: The recognition that a partner or caregiver is typically the patient's primary support person and is also deeply affected by the cancer diagnosis has prompted efforts to document their unmet supportive care needs. This review aimed to: (1) quantify the prevalence of unmet needs reported by partners and caregivers, (2) categorise their unmet needs by domain and (3) identify the main variables associated with reporting more unmet needs. Methods: Manuscripts were identified through systematically searching electronic databases, checking the reference lists of retrieved publications, online searching of key journals and contacting researchers in this field. Results: Unmet need items across 29 manuscripts were clustered into six domains: comprehensive cancer care (prevalence 1.1%–96%), emotional and psychological (3%–93.2%), partner or caregiver impact and daily activities (2.8%–79%), relationship (3.7% and 58%), information (2.2%–86%) and spiritual (2%–43%). Studies of caregivers of palliative care or terminal patients often reported a higher prevalence of unmet needs than studies of caregivers of cancer survivors. Variables associated with higher unmet needs included being female, not being the spouse of the patient, having lower social support or reporting distress. Conclusions: Despite the ability to classify unmet needs within broad domains, quantification of unmet needs was challenging. This was mainly due to the diversity in methods used across studies (eg, different measures, variability in conceptualisation of unmet needs, etc). Rigorous, context-specific, longitudinal studies that use validated measures are needed to benefit future intervention research.